2016
DOI: 10.1186/s12866-016-0870-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibiotic resistant Escherichia coli obtained from drinking water sources in northern Tanzania: a cross-sectional study

Abstract: BackgroundAntimicrobial resistance (AMR) is a growing and significant threat to public health on a global scale. Escherichia coli comprises Gram-negative, fecal-borne pathogenic and commensal bacteria that are frequently associated with antibiotic resistance. AMR E. coli can be ingested via food, water and direct contact with fecal contamination.MethodsWe estimated the prevalence of AMR Escherichia coli from select drinking water sources in northern Tanzania. Water samples (n = 155) were collected and plated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 30 publications
(32 reference statements)
5
41
2
3
Order By: Relevance
“…Similar to the previous study carried out in three European countries to establish the clonality of ESBL‐ E. coli in humans, animals and food animals (Wu et al., ), bla CTX‐M‐group 1 in particular bla CTX‐M‐15 was the predominant allele in this review. Predominance of bla CTX‐M‐15 allele is in agreement with bacterial strains from drinking water sources in Tanzania, and clinical isolates in the North, West and South African countries such as Tunisia, Nigeria and South Africa (Lyimo et al., ; Storberg, ). However, this was different from bla CTX‐M‐2 in flamingos exported to Japan from Tanzania and bla CTX‐M‐14 in a nearby East African country, Kenya in urine specimens (Sato et al., ; Storberg, ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Similar to the previous study carried out in three European countries to establish the clonality of ESBL‐ E. coli in humans, animals and food animals (Wu et al., ), bla CTX‐M‐group 1 in particular bla CTX‐M‐15 was the predominant allele in this review. Predominance of bla CTX‐M‐15 allele is in agreement with bacterial strains from drinking water sources in Tanzania, and clinical isolates in the North, West and South African countries such as Tunisia, Nigeria and South Africa (Lyimo et al., ; Storberg, ). However, this was different from bla CTX‐M‐2 in flamingos exported to Japan from Tanzania and bla CTX‐M‐14 in a nearby East African country, Kenya in urine specimens (Sato et al., ; Storberg, ).…”
Section: Discussionsupporting
confidence: 61%
“…Two strategies were employed in assessing potential bias in eligible studies, and as a result, two studies (Doijad et al., ; Mshana, Gerwing, et al, 2011) were excluded because they were conducted during an outbreak involving one strain of Enterobacter spp. Also, five studies were excluded because they included only genotypic detection of ESBL (Lyimo et al., ; Madoshi et al., ; Doijad et al, ; Mshana, Gerwing, et al., ; Sato et al., ), inclusion of these studies would have resulted into involvement of ESBL strains containing ESBL genes which are not expressed phenotypically (Figure ). Nevertheless, contributions of these studies were appraised and discussed in this review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterobacteriales has also been reported in up to 34% of healthy individuals (13) and high rates of antibiotic-resistant E. coli have been found in drinking water sources in Tanzania (14). The number of bacterial isolates was, however, low in this study and the bacteria were not identified to species level.…”
contrasting
confidence: 54%
“…Resistance to antimicrobial agents in clinically relevant Gram-negative bacteria is an increasingly important problem, which in the last few years has spread from the hospital setting to the community (Ghai & Ghai, 2018;Martínez-Martínez & Calvo, 2010). The emergence of antimicrobialresistant bacteria presents a major threat to public health because it reduces the effectiveness of antimicrobial treatment, leading to increased morbidity, mortality, and healthcare expenditure (Lyimo, Buza, Subbiah, Smith, & Call, 2016). Studies have shown the prevalence of antibiotic-resistant pathogens in wastewaters discharged into water bodies (Guardabassi, Petersen, Olsen, & Dalsgaard, 1998;Pruden et al, 2006;Quach-Cu, Herrera-Lynch, Marciniak, & Adams, 2018;Reinthaler et al, 2003), leading to the challenges in antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%